Electrical properties and thermal stability in stack structure of HfO2/Al2O3/InSb by atomic layer deposition - Baik, Min; Kang, Hang-Kyu; Kang, Yu-Seon; Jeong, Kwang-Sik; An, Youngseo; Choi, Seongheum; Kim, Hyoungsub; Song, Jin-Dong; Cho, Mann-Ho (NATURE PUBLISHING GROUP, 2017)
Changes in the electrical properties and thermal stability of HfO2 grown on Al2O3-passivated InSb by atomic layer deposition (ALD) were investigated. The deposited HfO2 on InSb at a temperature of 200 degrees C was in an amorphous phase with low interfacial defect states. During post-deposition annealing (PDA) at 400 degrees C, In-Sb bonding was dissociated and diffusion through HfO2 occurred. The diffusion of indium atoms from the InSb substrate into the HfO2 increased during PDA at 400 degrees C. Most of the diffused atoms reacted with oxygen in the overall HfO2 layer, which degraded the capacitance equivalent thickness (CET). However, since a 1-nm-thick Al2O3 passivation layer on the InSb substrate effectively reduced the diffusion of indium atoms, we could significantly improve the thermal stability of the capacitor. In addition, we could dramatically reduce the gate leakage current by the Al2O3 passivation layer. Even if the border traps measured by C-V data were slightly larger than those of the as-grown sample without the passivation layer, the interface trap density was reduced by the Al2O3 passivation layer. As a result, the passivation layer effectively improved the thermal stability of the capacitor and reduced the interface trap density, compared with the sample without the passivation layer.
Keywords: OXIDE; INTERFACE; EVOLUTION; CHARGE; FILMS; GAAS; INP